Wireless internet : 8th International Conference, WICON 2014, Lisbon, Portugal, November 13-14, 2014, Revised selected papers /: 8th International Conference, WICON 2014, Lisbon, Portugal, November 13-14, 2014, Revised selected papers. (2015) - Unknown
No abstract available